hAMSC Sheet Promotes Repair of Rabbit Osteochondral Defects - Gang Zou; Jun Zhang; Qifan Yang; Xiaoyan Wang; Pengpeng Sun (Hindawi Limited, 2022)
Osteochondral lesion is clinically common disease, which has been recognized as one of the contributing factors of significant morbidity. Although current treatments have achieved good outcomes, some undesirable complications and failures are not uncommon. Cell sheet technology (CST), an innovative technology to harvest seed cells and preserve abundant ECM, has been widely used in various tissue regeneration. For osteochondral lesion, many studies focus on using CST to repair osteochondral lesion and have achieved good outcomes. In the previous study, we have demonstrated that hAMSC sheet had a positive effect on osteochondral lesion. Therefore, this study is aimed at comparing the effect of noninduced hAMSC sheet with chondrogenically induced hAMSC sheet on osteochondral lesion and cartilage regeneration.